Investigation on the retentive force and fatigue property of different designed polyetheretherketone clasps - LUO Yichen, QIU Lin, GENG Mingzhu, ZHANG Wei (Kouqiang yixue, 2024)
Objective By investigating the retention and fatigue performance of polyetheretherketone(PEEK) clasps with increased proportions of clasp arm engaging the undercut, an innovative method to improve PEEK clasps’ performance was proposed and verified. Methods Three groups of PEEK clasps(n=10/group) with the terminal 1/3, 2/3 and whole of their retentive arms engaging the 0.75 mm undercut were designed and fabricated respectively along with a group of cobalt-chrome clasps(n=10) with their terminal 1/3 of retentive arms engaging the 0.25 mm undercut. Retentive forces were recorded initially and every 1 500 cycles for a total of 15 000 insertion and removal fatigue cycles. Optical scanning and software analysis were applied to evaluate the deformation of the clasps by root mean square (RMS) after fatigue test. The inner surface morphology of clasps’ arms was observed by scanning electron microscopy. Results PEEK clasps with the whole of their retentive arms engaging the undercut exhibited highest mean retentive force (9.24±1.78) Namong other PEKK clasps, which was slightly lower than that of cobalt-chrome clasps (11.88±2.05) N. The retentive force of each group turned out to be reduced after fatigue cycles and cobalt-chrome clasps showed the greatest reduction (38.38%). The RMS of the PEEK clasps groups were of no statistical difference (P=0.111) and were lower than that of cobalt-chrome clasps (105.47±10.82) μm. Evidence of surface abrasion was observed on all groups of clasps especially on the section that engaged the undercut. Conclusion Increasing the proportion of PEEK clasp arm engaging the undercut effectively improved the retentive force and satisfied clinical requirements after fatigue cycles. PEEK clasps exhibited greater retention stability than cobalt-chrome clasps. It is feasible to improve the performance of PEEK clasps by increasing the proportion of clasp arm engaging the undercut.